Creatinina y proteinuria como indicador de la función renal en diabéticos. Hospital General Docente Ambato. mayo 2017- junio 2018. - María Graciela, Pomavilla Chimborazo (2018)
The kidney performs several interrelated functions that depend on the glomerular filtration rate. The objective of this investigation was to analyze the results of creatinine and proteinuria as an indicator of renal function in diabetics of the General Teaching Hospital of Ambato. This project was not descriptive, explanatory, transversal retrospective type and mixed character it was worked with qualitative and quantitative characteristics of the tests, the population consists of 2027 results creatinine and proteinuria, by applying statistical formula, The inclusion and exclusion criteria, 52 study results were obtainet as a study sample from diabetic patients who performed the two tests described simultaneously. Data collection and analysis techniques and instruments were used, such as information registration forms and the Excel statistical program. As a result, it was found that there is a greater demand for creatinine results in relation to proteinuria, more female results than male. According to the state of the people, 87% constitute beneficiaries without diabetes, while 13% represent people with diabetes, a significant percentage with which it was confirmed that in the hospital there are people with this pathology, who perform repeated controls, in many of them with an improvement, as with medical control and treatment they return to have the values within the reference parameters. Finally, it is concluded that the data obtained are reliable since in the laboratory they comply with the quality control and maintenance protocols of the Roche / Hitachi cobas c501 analyzer.